Effects of Replacing Lactose with Novel Carbohydrate Sources on Nursery Pig Growth Performance - Rafe Q. Royall; Jason C. Woodworth; Mike D. Tokach; Joel M. DeRouchey; Jordan T. Gebhardt; Robert D. Goodband; Keith Mertz; John F. Patience (Kansas Agricultural Experiment Station Research Reports, 2022)
This experiment was conducted to determine the effects of replacing lactose in Phase 1 and 2 nursery pig diets with 1 of 2 novel carbohydrate (CHO) products (CHO-D and CHO-L; Cargill Starches, Sweeteners, & Texturizers, Blair, NE) on growth performance and fecal dry matter. A total of 360 barrows (DNA 200 × 400; initially 13.2 ± 0.10 lb) were used in a 42-d growth trial. Pigs were weaned at approximately 21 d of age, randomly allotted to pens in 1 of 2 weight blocks based on initial BW (initially 12.0 and 14.5 lb), and then allotted to 1 of 6 dietary treatments in a completely randomized design. There were 5 pigs per pen and 12 pens per treatment across 2 barns. Dietary treatments were corn-soybean meal-based with 5 to 7.5% DDGS and included: 1) negative control (NC; containing 0.08 and 0.04% lactose, phase 1 and 2, respectively); 2) positive control (PC; containing 10 and 5% lactose, phase 1 and 2, respectively); 3) 50% of lactose replaced with the dry novel CHO (50% CHO-D; containing 5 and 2.5% lactose, phase 1 and 2, respectively); 4) 100% of lactose replaced with CHO-D (100% CHO-D; containing 0.09 and 0.05% lactose, phase 1 and 2 respectively); 5) 50% of lactose replaced with the liquid novel CHO (50% CHO-L; containing 5 and 2.5% lactose, phase 1 and 2, respectively); or 6) 100% of lactose replaced with CHO-L (100% CHO-L; containing 0.09 and 0.05% lactose, phase 1 and 2, respectively).Treatment diets were formulated in two dietary phases and fed from d 0 to 10 and d 10 to 24, respectively, with a common phase 3 diet fed for the remainder of the study. During the treatment period (d 0 to 24) there was a weight block × CHO source interaction (P= 0.045) on ADFI, in which heavyweight pigs fed the PC diet had greater (P= 0.001) ADFI than lightweight pigs fed the same diet, while there was no significant difference due to weight block among any other CHO sources. Furthermore, overall (d 0 to 42) there was a tendency for a weight block × CHO source interaction (P= 0.067) on ADFI. Additionally, pigs in the heavyweight block had greater (P≤ 0.001) BW, ADG, and ADFI compared to pigs in the lightweight block throughout the experiment. However, overall, pigs from the lightweight block had improved (P= 0.033) feed efficiency compared to pigs in the heavyweight block. There was a tendency for a main effect of CHO source (P= 0.057) on feed efficiency during the treatment period, in which pigs fed the NC diet had the lowest numeric F/G and pigs fed the 100% CHO-L diet had the highest numeric F/G. However, this did not persist throughout the overall study (P= 0.329). Additionally, there was no observed main effect of CHO source (P>0.100) on ADG or ADFI throughout the overall study. In summary, feeding either of the novel CHO sources did not significantly affect growth performance, percentage of pigs that lost weight post-weaning, or fecal dry matter during nursery period compared with those pigs fed a traditional lactose source or a diet that did not contain any lactose. Based on the results herein, pigs fed diets containing either novel CHO product had equivalent performance to those on the PC treatment, but we were unable to detect incremental value as the PC treatment did not significantly differ from the NC treatment.
Keywords: carbohydrate; fecal dry matter; growth; nursery pig